Efforts of The Nagari Taram Government in Improving Community Welfare Through Kapalo Banda Tourism - Dinda Novita Putri; Zainal Fadri; Iswadi Iswadi; Beni Putra Hanafi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem in this study is the effort to improve community welfare through the development of Kapalo Banda tourism. Limited basic infrastructure such as inadequate road conditions and minimal supporting facilities are the main obstacles. Access roads to the location of tourist attractions are still in poor condition, there is a lot of damage and obstacles making it difficult for tourists to reach them. infrastructure problems, management of Kapalo Banda tourism objects by the Taram regional government has also not been implemented optimally. The type of research used by the researcher is field research using qualitative descriptive research methods to obtain data from the problems studied. Kapalo Banda tourism has created new jobs for the community, thereby reducing unemployment in the area. The economic impact of Kapalo Banda tourism development improves the quality of life of the community, increasing the standard of living and social welfare of the Nagari Taram community. Kapalo Banda tourism has a positive impact on the economy and social welfare of the community. get increased income, job opportunities and a better quality of life. Kapalo Banda tourism has created new jobs for the community, thereby increasing job opportunities, reducing unemployment. The development of Kapalo Banda tourism has increased community income, both from the tourism sector and other economic sectors related to the existence of tourist attractions.